Desain Rute dan Optimasi Biaya Transportasi Pengisian Tabung Oksigen menggunakan Metode Complete Enumeration pada CV. Tasman Gases - Az-Zahra, Vira Luthfiati; Dewy, Cyndy Kresna; Fikri, Muhammad Albi; Fauzi, Muchammad (Universitas Kadiri, 2023)
The increasing demand for filling oxygen cylinders makes CV. Tasman Gases has always been consistent in planning transportation cost optimization strategies. The filling of oxygen cylinders in one distribution can transport up to 45 tubes sent to the concerned partner. The purpose of this study is to determine the shortest route and optimal cost in distributing. The method used is Complete Enumeration. The samples used include distribution locations and mileage. The procedure used begins with determining the number of routes, estimated mileage and fuel costs. There is the most optimal route selected from the 12 modeled routes. The selected route has the least transportation costs. This research makes CV. Tasman Gases has the best route, A-D-C-E-F with a distance of 10.9 km worth Rp. 10,423.13.Â This value is more effective than the existing A-E-C-D-F condition with a distance of 12.8 km obtaining fuel costs of Rp. 12,240.00. Thus, the distribution route and costs that have been optimal make CV. Tasman Gases can implement and identify future transportation constraints.